QUANTIFICATION OF N-ACETYLNEURAMINIC ACID( NEU5AC) IN HUMAN MILK USING N- GLYCOLYLNEURAMINIC ACID AS INTERNAL STANDARD BY LC-MS/MS - D.KARUNANITHI,; A.RADHAKRISHNA,; V.M.BIJU, (International Journal of Pharma and Bio Sciences, 2012)
A rapid, reliable and sensitive LC-MS/MS method for the determination of N-acetylneuraminic acid (Neu5Ac) in human milk was developed and validated. Samples were hydrolysed with mild hydrochloric acid and analysed by LC-MS/MS on Thermo hypersilgold C-18 analytical column. The analytical procedure was found to be more selective, accurate, precise and linear. The method accuracy was 99.9 % and the mean precision (RSD) was 3.51 % and the calibration was linear from 0.1 to 10 µg mL-1 (R2> 0.99), the lowest limit of quantification (LLOQ) was 0.1 µg mL-1 . N-glycolylneuraminicacid (Neu5Gc) was used as an internal standard. This method was proved as promising method for the determination of Neu5Ac in human milk samples.